PERAN SENI KLASIK DALAM KEBUDAYAAN ISLAM - Abdullah, Dindin Sofyan; Al Ayyubi, Ibnu Imam; Rohmatulloh, Rifqi (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2021)
Islam is closely related to the aesthetics of classical art, this is enlivened by elements of culture that have such a large influence on various fields, including the fields of education, language, law, politics, philosophy, ethics, rhetoric, and art itself. Classical art is a manifestation of fine art made by the people according to the culture in a certain area for generations, inherent in the flesh so it is difficult to experience significant changes from time to time. The method used in this study is a descriptive qualitative research method with a literature study approach that refers to several research data sources and data collection techniques in the form of studies of Islamic classical art. The focus of the research that will be raised is the role of classical art in Islamic culture. The data collection technique used in this study was the library research method, namely library research and the data analysis technique used in this study was a descriptive method. Based on the research conducted, it can be concluded that classical art is inherent in Islamic religious culture, where there are ritual ceremonies that are thick with the Islamic religion, both in primitive and classical styles.